Neonatal mortality related to prematurity (Research, Society and Development, 2022)
Objective: Demonstrate the increase in neonatal mortality rates from preventable causes and its relationship with premature birth. Methodology: This is a descriptive study with a quantitative approach, developed from secondary data from the mortality information system (SIM) available at the Department of Informatics of the Brazilian National Health System (DATASUS). Results: In the year 2019 neonatal mortality for extreme immaturity and preterm newborn prevailed 877 cases (57.1%) over the total deaths referring to gestational disorders of short duration, corresponding to 600 cases (39%) of deaths for extreme immaturity and 277 cases (18%) of deaths for preterm neonates. Discussion: It is observed that in Brazil the highest rate of neonatal mortality is related to the ICD 10 P07 indicator that refers to disorders related to gestation of short duration and low birth weight. Conclusion: It is important to emphasize that even if there is inadvertence in the computation of the notification of these data, there is still a high number of cases in this category, because it is a public health problem that affects pregnant women and their families nationwide.